Artificial additives and preservatives usage amongst female staffers of Nwafor Orizu College of Education Nsugbe and their health implications - Emeka, Ebele Cynthia; Ibedu, Esther Chiagozie (World Health Digital Journal, 2025)
The study investigated the food additives and preservatives usage amongst female staffers of Nwafor Orizu College of Education Nsugbe and their health implications. The main objective of this study is to identify and ascertain the artificial additives and preservatives used by female staff members of Nwafor Orizu College of Education Nsugbe in food processing and the health implications that can arise from their usage.  Three research questions guided the study. The instrument for data collection was a four-point structured questionnaire which was validated as well as tested for reliability using the split half reliability method which yielded a coefficient of 0.83. Instrument was administered primarily and data were analyzed using mean and standard deviation. The study revealed that the female staffers of NOCEN are familiar with some of the additives and preservatives used in food processing such as aspartame, monosodium glutamate etc.  It was revealed also that indiscriminate use of these additives can raise health concerns like triggering asthma and respiratory defect symptoms. The study conducted that the respondents are aware of and consume artificial additives and preservatives used in food processing. They are also in the know of some health implications that may arise from their use. Based on the findings and conclusion it is suggested that consumers use these additives in moderation, health and consumer agencies should always update the reviews on their usage